Defining the 'new terrorism': Reconstruction of the enemy in the global risk society ['Yeni terörizm'i tani{dotless}mlamak: Küresel risk toplumunda düşmani{dotless}n yeniden yapi{dotless}landi{dotless}ri{dotless}lmasi{dotless}] - (:unkn) unknown (My University, 2012)
Employing the conceptual frameworks provided by Ulrich Beck and Carl Schmitt; this article argues that the reconstruction of the enemy in the global risk society reflects a reincarnation of a "crude" form of "the political". As the powerful -the US- determines our knowledge on global terrorism, the global risk society itself becomes political, through the reconstruction of the enemy as inhuman and, thus, right-less: an enemy who should be captured and punished severely. This also refers to a deconstruction of the classical conception of war and its reconstruction as a special kind of war which involves the use and legitimization of measures that violate all rules of war, international law and human rights. This article concludes that attempts to define the "new terrorism" on positivist lines risk contributing to such reconstruction of the enemy and war, and, therefore, critical and post-structuralist approaches might offer more insight into understanding the post-9/11 world. © International Relations Council of Turkey (UİK-IRCT).
Keywords: Enemy; Global risk society; Terrorism; The political; War